Multifunctional Baicalin-Modified Contact Lens for Preventing Infection, Regulating the Ocular Surface Microenvironment and Promoting Corneal Repair - Luo, Yue; Liu, Luying; Liao, Yuzhen; Yang, Ping; Liu, Xiaoqi; Lu, Lei; Chen, Jiang; Qu, Chao (Frontiers in Bioengineering and Biotechnology, 2022)
Corneal injury inevitably leads to disruption of the ocular surface microenvironment, which is closely associated with delayed epithelial cell repair and the development of infection. Recently, drug-loaded therapeutic contact lenses have emerged as a new approach to treating corneal injury due to their advantages of relieving pain, promoting corneal repair, and preventing infection. However, few therapeutic contact lenses could modulate the ocular surface's inflammation and oxidative stress microenvironment. To address this, in this study, we covalently immobilized multifunctional baicalin (BCL), a flavon molecular with anti-inflammatory, anti-oxidative stress, and antibacterial capabilities, onto the surface of the contact lens. The BCL-modified contact lens showed excellent optical properties, powerful antibacterial properties, and non-toxicity to endothelial cells. Furthermore, the BCL-modified contact lens could significantly modulate the ocular surface microenvironment, including inhibition of macrophage aggregation and resistance to epithelium damage caused by oxidative stress. In animal models, BCL-modified corneal contact lens effectively promoted corneal epithelial cells repair. These excellent properties suggested that multifunctional BCL molecules had great application potential in the surface engineering of ophthalmic medical materials.